Can we make the predonation screening process more effective?. (29th January 2016) - Norda, R.; Frazzetto, M. L.; Lubenow, N.; Knutson, F.
Abstract : Blood establishments are responsible for the quality and safety of the blood collected and the final acceptance or deferral of a donor. All donors must undergo a screening process just prior to the blood donation. The elements are: (i) Identification of the donor and linking the identity to all the relevant documentation. (ii) Information timely provided so that the donor can decide whether to donate or to abstain. (iii) The donor health history must be evaluated by a questionnaire and complementary questions. (iv) The donor signs to confirm his/her responses. (v) A few physical parameters are assessed. (vi) Blood samples are collected for hemoglobin and markers for infectious agents. The questionnaire serves to detect exposures to hidden problems with possible consequences for the recipient. The interview clarifies answers and if the donor understood the information. Laboratory investigations of primary importance to the recipient involves screening assays for antigens, antibodies and RNA/DNA as legally required. Continuous improvement has led to shortening of the undetectable infectious period. There is continuous vigilance for emerging new infections or re‐emerging 'old' infections leading to modified deferral rules and development of new screening tests. In recent years there has also been modification of deferral criteria concerning sexual behavior with high risk for acquiring transfusion transmitted infections (TTI). Modelling of the risks of TTI in any given epidemiological situation and estimates of donor compliance precedes changes. Tools to study the effectiveness of the pre‐donation screening process include evaluation of recalled units, verified screening‐positive donors and compliance studies.